Pleurothallis inaudita, an unnoticed new species in Pleurothallidinae (Orchidaceae) from southwestern Ecuador - Romero, Bosco Javier Zambrano; Solano, Rodolfo (Phytotaxa, 2023)
A new orchid species in Pleurothallis subsection Acroniae, is described and illustrated from Ecuador. Information concerning its distribution, habitat and phenology is provided. The new taxon is named as P. inaudita and is compared with the most similar species, P. imitor, from which it differs by its amber flowers suffused with red-purple (vs. yellow), lanceolate dorsal sepal (vs. ovate), ensiform petals (vs. oblong-subfalcate), and an ovate-triangular lip with an oblate callus (vs. triangular-sagittate with an oblong callus). Furthermore, P. inaudita is compared with P. tryssa and other morphologically similar species, member of Pleurothallis subsection Macrophyllae-Fasciculatae, P. crucifera.